Translational movement of the eyeball under the influence of an air impulse - Chigarev AV; Mikhnovich MO (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2023)
The study of the biomechanics of the eye is important for understanding the mechanisms of its functioning and the causes of the development of pathologies. New knowledge helps to better diagnose a number of diseases and develop effective methods for their treatment. The theoretical results obtained can give impetus to new research in this area.  In this paper, the displacement of the eyeball as a whole body along the optical axis is considered.